Chrzest jako pieczęć - Słomka, Jan (Śląskie Studia Historyczno-Teologiczne, 2007)
Judeo-Christian writings introduce the concept of a „seal” as one of the basic terms defining Baptism. It is related to the Jewish apocalyptics and the Apocalypse. In that context, the „seal” is identified with the Name of Jesus. As the Judeo-Christian tradition gradually vanishes, the identification of the seal with the name of Jesus also disappears. Instead, there is a return to the theology of St Paul, who wrote about being sealed by the Holy Spirit. The image of Baptism as the seal of the Holy Trinity also begins to appear. In the Latin literature of the 3rd century, the concept gradually assumes the form of a separate rite – being anointed by a bishop – thus, it is more and more strongly associated with the granting of the Holy Spirit. In the 4th century, the term „seal” is no longer used in relation to Baptism. It continues to define Baptism in the East, but in the 4th century, apart from Cyril of Jerusalem, very few people use it. It is carefully avoided by the Fathers following the Alexandrian tradition, John Chrysostom of Antiochia does not seem to like it, either.